Impact of Acquisition of Digital Skills on Perceived Employability of Youth: Mediating Role of Course Quality - Daisy Mui Hung Kee; Aizza Anwar; Sai Ling Gwee; Muhammad Fazal Ijaz (Information, 2023)
Penang Youth Development Corporation took the “Penang Young Digital Talent Program” initiative to bridge the gap between Malaysian youth’s current digital skills and emerging technologies market demands. The program comprises different online courses such as web design, digital marketing, etc. The objective of this study is to understand the level of participants’ digital competency and, secondly, investigate the impact of participants’ digital competency on their perceived employability and examine the mediating role of course quality. This study employed a cross-section design method, and data were collected using purposive sampling. The participants (Nn= 385) of this program range from 18 to 22 years old, either born in Penang or have resided in Penang for a minimum of 3 years. The data were analyzed using Smart PLS 3.0. Post-online course findings show that digital content creation, information and data literacy, and problem-solving have a significant and positive relationship with perceived employability. Moreover, course quality significantly mediates the impact of communication and collaboration, digital safety and information and data literacy on the perceived employability of Malaysian youth. The findings of this research have implications for policymakers responsible for education, emphasizing youth’s acquisition of digital skills to help them succeed in the current workplace.